Post-traumatic lung pseudocysts: two case reports in ICU patients - Voutsas, Vasileios; Giakamozis, Athanasios; Lazaridis, Theoharis; Bitzani, Milly (Journal of Thoracic Disease, 2012)
Introduction: The traumatic lung pseudocyst is a rare complication of closed thoracic injury. We present two cases with traumatic lung pseudocyst who were admitted in our ICU. Case 1: A 19 year old man was admitted in the ICU after a motorcycle accident. Chest CT revealed two well defined densities in the right upper lung lobe with presence of air bubbles within them. Four days after admission chest CT showed two cavitary lesions in the upper lobe. The patient showed gradual clinical improvement. Repeated chest CT after 6 months was normal. Case 2: A 41 year old man was involved in a car-bicycle accident. The patient was admitted in the ICU with respiratory failure and flail chest. Chest CT revealed multiple bilateral rib fractures, right pneumothorax and contusions of the right lung. Two days after admission chest CT showed formation of lung pseudocyst. The patient was gradually stabilised and 22 days after the accident the chest CT revealed resolution of the pseudocysts. Discussion: The traumatic lung pseudocyst is a rare complication of blunt thoracic trauma. The clinical course of traumatic lung pseudocyst is usually benign, unless complications such as pneumothorax or infection of the cavitary lesion arise. These lesions are more common in children and young adults.